An intelligent and simplified 5G wireless network technology - Yuhong HUANG; Qi SUN; Minli JIA; Ran DUAN; Zhuo CHEN (Dianxin kexue)
5G is the current focus of the development of the information and communication industry, and is gradually being deployed and commercialized.The 5G network will cover toC to toB, aiming at the interconnection of everything, so the complexity and challenges are unprecedented.In order to meet the needs of multiple scenarios, 5G network technology is complex and flexible in design, and the traditional management and operation methods are difficult and costly.At the same time, industry application requirements are very different and demanding.All of these require integrated solutions such as cloud-network integration and network industry collaboration.In response to the above-mentioned problems and needs, an intelligent and simplified 5G wireless network technology framework was proposed.Through innovative thinking and technology development of wireless networks, 5G and artificial intelligence, cloud computing, big data, edge computing and other new technologies were integrated and innovated to continuously improve 5G capabilities and promote the deep convergence of 5G and DOICT.A detailed introduction to the entire framework, platforms and applications in the above technology system were given.Finally, a technical outlook was proposed for shaping a new 5G ecology that supported green, smart, efficient operation, and the internet of everything.